(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
The experiment was conducted to evaluate the adaptability of newly released papaya varieties at Chano Mille research site of Arba Minch Agricultural Research Center during 2019-2020 cropping seasons. The three hermaphrodite papaya varieties namely; Braz-HS1, Koka-HM1 and Meki-HL1 were used for the study and laid-out in a Randomized Complete Block Design in three replications. Data on yield and yield components were collected and analyzed by using analysis of variance (ANOVA) through Statistical Analytics System software. The ANOVA results revealed that there were significant variations among papaya varieties for the studied parameters. Significantly, the highest number of fruits plant-1, number of leaves and fruit yield were obtained from Braz-HS1 papaya variety. The fruit yield of Braz-HS1 variety was 46% higher than that of Koka-HM1. In general, Braz-HS1 papaya variety performed (in terms of number of fruits and fruit yield) better than the rest two varieties. Thus, Braz-HS1 papaya variety could be recommended for the papaya growers in the study area and vicinity with similar agro-ecology. Int. J. Agril. Res. Innov. Tech. 11(2): 69-71, Dec 2021